MODEL IMPROVEMENT OF MESSAGE SECURE ROUTING WITH OPTIMAL BALANCING ITS FRAGMENTS NUMBER TRANSMITTED OVER NON OVERLAPPING PATHS - Лемешко, Олександр Віталійович; Єременко, Олександра Сергіївна (Ukrainian Information Security Research Journal, 2015)
The given work is devoted to improvement andinvestigation of secure routing model with optimalbalancing of message fragments number in mobile selforganizingnetworks. Within the work it was explored theconcept of threshold secret sharing scheme in relation tosecure routing using non overlapping paths for themessage frag-ments transmission. Based on analysis ofdisadvantages of existing mechanism SPREAD it wasproposed the im-provement of fragments allocationmodel which had been reduced to the optimal balancingof message fragments number transmitted over the nonoverlapping paths. It was proposed several optimalitycriterions related to the so-lution of balancing problem.In a comparative analysis it is justified to use on practiceoptimality criterion, providing on the one handminimizing dynamically managed upper bound number offragments transmitted over separate non overlappingpaths in the network, and from the other hand – to adaptto security parameters (probability of compromise) ofindividual network elements: nodes, links and paths.Numerical examples of models with different optimalitycriterion of the solutions obtained, and their comparativeanalysis represented. The comparison results confirmed the effectiveness of the proposed model, when by theworst path in terms of the probability of com-promisetransmitted the minimum number of fragments, and bythe best path – their maximum number.